Neonatal toxoplasmosis in dogs and kittens - Bresciani, Katia Denise Saraiva [UNESP]; Galvão, André Luiz Baptista [UNESP]; de Vasconcelllos, Amanda Leal [UNESP]; de Matos, Lucas Vinicius Shigaki [UNESP]; Pierucci, Julia Cestari [UNESP]; de Koivisto, Marion Burkhardt [UNESP]; Sakamoto, Claudio Alessandro Masamtsu [UNESP]; Soares, José Antonio; dos Santos, Thais Rabelo [UNESP]; da Costa, Alvimar José (My University, 2014)
The protozoan parasite Toxoplasma gondii commonly infects cats, dogs and humans. Toxoplasmosis is an important issue concerning public health, particularly involving the risk of disease transmission during pregnancy. The infection can be acquired by ingestion of tissue cysts in infected meat, ingestion of food or water contaminated with oocysts and congenitally, by tachyzoites crossing the placenta from the infected mother to the fetus. Congenital T. gondii infection has been reported in many species of animals. The organism strain, dose, and the stage of fetal development or age of the host at the time of infection likely influence the presence or severity of clinical toxoplasmosis in the neonate. The infecting stage of the organism (tachyzoite, oocyst, cyst) may also be important. Uterine changes were observed in bitches with toxoplasmosis (endometritis). Cats with disseminated organism replication which in clinical toxoplasmosis usually have multiple organ involvement that commonly includes the eyes. Ocular toxoplasmosis can occur without other evidence of clinical illness in kittens infected in uterus or in the neonatal period, and T. gondii strains may have varying degrees of ocular pathogenicity in cats. The aim of this chapter will be to elucidate some clinical neonatal aspects in view of congenital toxoplasmosis in cat and dog.